LIBER Licensing Principles for Electronic Information - Klugkist, Alex C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Publishers are working on or are considering - with or without the intervention of libraries - activities such as storage, disclosure and provision of access that traditionally belong to the field of work of libraries. By using the new scope that information technology offers, they try to defend their position in the field of information and, if possible, to strengthen it.